Robust volleyball tracking system using multi-view cameras - Takahashi, M.; Ikeya, K.; Kano, M.; Ookubo, H.; Mishina, T. (2016 23rd International Conference on Pattern Recognition (ICPR), 2016)
We have developed a real-time ball tracking system that can be used for volleyball games. Although a number of methods for visual object tracking have been proposed, tracking a fast-moving ball is still a challenging task because of the motion blur and the occlusion. We thus use a complementary tracking scheme in which tracking processes for multiple cameras help each other sharing the 3D position of the ball. The ball on each camera is accurately tracked by predicting its position at the next frame. The 3D ball positions measured by the system can be used for drawing the trajectory CG of a ball and for calculating statistical data related to ball movement. Evaluation results obtained using actual volleyball video sequences showed that the system would be effective for visualizing ball trajectories in live volleyball broadcasts.